A novel method for biopolymer surface nanostructuring by platinum deposition and subsequent thermal annealing - Slepička, Petr (Springer, 2012)
A novel procedure for biopolymer surface nanostructuring with defined surface roughness and pattern dimension is presented. The surface properties of sputtered platinum layers on the biocompatible polymer poly(l-lactic acid) (PLLA) are presented. The influence of thermal treatment on surface morphology and electrical resistance and Pt distribution in ca. 100 nm of altered surface is described. The thickness, roughness and morphology of Pt structures were determined by atomic force microscopy. Surface sheet resistance was studied by a two-point technique. It was the sequence of Pt layer sputtering followed by thermal treatment that dramatically changed the structure of the PLLA’s surface. Depending on the Pt thickness, the ripple-like and worm-like patterns appeared on the surface for thinner and thicker Pt layers, respectively. Electrokinetic analysis confirmed the Pt coverage of PLLA and the slightly different behaviour of non-annealed and annealed surfaces. The amount and distribution of platinum on the PLLA is significantly altered by thermal annealing.